Simone Weil et les dimensions mystiques de la nourriture - Salihbegovic, Nejra (Labyrinth, 2024)
This article aims to examine the mystical meanings of food in the texts Gravity and Grace, Waiting for God, and First and Last Notebooks by the French philosopher Simone Weil (1909-1943). The main questions posed over the course of this study are as follows: How does Weil interpret food in her mystical texts? What relationship do her ideas have with her context of the Second World War, with Judaism, with her body? Are biomedical understandings of behavior, such as anorexia nervosa, applicable to Weil? The methodology will involve an in-depth reading of the three texts mentioned above, sketching the key theories of decreation and affliction. The main thesis of the paper is that food has an irremediably ambiguous status in Weil, marking both the degrading subjection of the human being to the earthly laws of necessity and gravity, and paradoxically, a path to salvation, where, through the spiritual transformation of decreation, the human being eats and is eaten by God. The author argues that this quasi-Christian mysticism must first be understood in Weil’s context of the Second World War, and that it also involves a problematic relationship with Judaism. Moreover, this study contends that interpretations utilizing primarily medical frameworks to understand Weil's food deprivation, such as anorexia nervosa, are insufficient. Such pathologization, as will be demonstrated, neglects the complex and often ambiguous mystical, ethical, and ontological meanings that Weil locates in hunger.